Penatalaksanaan altered passive eruption dengan crown lenghtening (Laporan Kasus) - Luki Astuti (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Aesthetic treatments related to the perfect smile are important in contemporary clinical dentistry. The disharmony of the smile, often called the gummy smile, can be caused by vertical maxillary growth, dentoalveolar extrusion, short upper lip, hyperactivity of the upper lip, altered passive eruption (APE), or a combination of such factors. Some studies mention the possibility of APE being a risk factor for periodontal disease. In some cases, excessive gingival can interfere with oral hygiene procedures and result in plaque accumulation and inflammation of the gingival margin. The management of APE is by periodontal crown lengthening surgery. The selection of the crown lengthening technique is adjusted to the classification, thickness, and number of keratinized gingiva, as well as the location of the cementoenamel junction (CEJ) or bone peak against the gingival margin.